Challenges and Opportunities for Biomarker Validation. Issue 3 (September 2019) - Hey, Spencer Phillips; D'Andrea, Elvira; Jung, Emily H.; Tessema, Frazer; Luo, Jing; Gyawali, Bishal; Kesselheim, Aaron S.
Biomarkers can be powerful tools to guide diagnosis, treatment, and research. However, prudent use of bio-markers requires formal validation efforts. Although the data needed for biomarker validation has traditionally been hard to access, new research initiatives can ease this process.